Chris Cunningham: corpo e dejeto no vídeo contemporâneo - Andrade, Sueli Chaves (2017)
Chris Cunningham is the main subject in this thesis. Cunningham was one of the most influential and creative music video directors in the 90’s and early 2000’s. Visible throughout his art is the theme of the body and its innards - an important and wide discussion in contemporary culture studies. The hypothesis of this text is that the music video is one of the main audiovisual narratives of postmodern culture from the aspect of new aesthetics and artistic experiments. Cunningham adds original marks to the characteristics that constitute contemporary art, especially the one that has placed the body under interrogation and also the art object as waste. The contemporary art discussion in this thesis is inspired by psychanalysts Jacques-Allan Miller and Gerard Wajcman and the positioning of the object, and a new gaze at it is provided by Didi-Huberman. Concerning the role of the body in this setting, Santaella brings a contribution on it as an art support, besides presenting much of the specific problems of the body in culture. Raymond Bellour, Philippe Dubois and Arlindo Machado with their discussions around film and video allow the insertion of the music video as a language with its own characteristics and history, as the theorists Andrew Goodwin, E. Ann Kaplan and Carol Vernallis point out. The Lacanian theory provides a formal way to analyze and discuss the body from an instinctive perspective that drives the subject in the contemporary world. In order to prove this assertion and the hypothesis of this thesis, three semiotic-psychoanalytic analyses were done on the following works: All is Full of Love (1999), Flex (2000) and Rubber Johnny (2005)